Development, Identification, and Application of a Germplasm Specific SCAR Marker for Dendrobium officinale Kimura et Migo - Zheng, Kaixin; Cai, Yuchen; Chen, Weijie; Gao, Yadi; Jin, Jingjing; Wang, Huizhong; Feng, Shangguo; Lu, Jiangjie (Frontiers in Plant Science, 2021)
The stems of Dendrobium officinale have been used as a rare and valuable Chinese tonic medicine, known as “Tiepi Fengdou”, since the Qing dynasty. Because of the increased market demand and continued exploitation of this plant, the reserves of wild D. officinale resources have been depleted, and D. officinale products on the market are being increasingly adulterated. Such changes have strongly affected the sustainable utilization of this valuable medicinal plant resource and the development of related industries. In this study, a species-specific DNA marker was developed for the rapid and accurate authentication of D. officinale. In total, 36 start codon-targeted (SCoT) polymorphism primers were screened in 36 definite Dendrobium species, and a distinct species-specific DNA amplicon (SCoT13-215) for D. officinale was obtained. After the sequence was cloned and sequenced, a sequence-characterized amplified region marker was developed (named SHF/SHR) and validated through PCR amplification of all 38 Dendrobium samples. The marker’s specificity for D. officinale was confirmed through the consistent amplification of a clear 197-bp band. This SCAR marker can be used to rapidly, effectively, and reliably identify D. officinale among various Dendrobium species and may play an important role in ensuring the quality of medicinal preparations and protecting the germplasm of this important medicinal species.